Human Identity in Helvétius’ Social Philosophy - Laskowski, Damian (Sensus Historiae, 2020)
In my article, I describe the issue of human identity from the perspective of the philosophy proposed by the Enlightenment philosopher Claude-Adrien Helvétius. I believe that his vision of society may be useful for those living in the 21st century, trying to build a functioning state, in which men will be able to fulfil everything that leads to happiness and, at the same time, contribute to the promising functioning of society. I present his vision of a man from the state of nature of society of the18th century France. I present what constitutes human identity and what makes a man realize a specific way of life in the world, connected with his social function and individual pursuit of happiness. I focus on how society affects an individual from birth to adult life, in which the main role is taken by the law, imposed by the rulers.